2021
DOI: 10.1177/10434542211011042
|View full text |Cite
|
Sign up to set email alerts
|

We are all a family” Staff Experiences of Working in Children's Blood and Cancer Centers in New Zealand—A Constructivist Grounded Theory

Abstract: Background: The purpose of this study is to explore staff experiences of working in a children's blood and cancer center in New Zealand, with a particular focus on how staff maintain resilience in their work and sustain working in this difficult area. Methods: Constructivist grounded theory (GT) methods were used to collect data using focus groups and individual interviews with all staff (nursing, medical, allied health, cleaning, and support staff) working in the area. Data were analyzed using constant compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
2
9
1
1
Order By: Relevance
“…Caring for young patients who are dying clearly requires emotional labour for all nurses, which is in keeping with the literature more broadly concerning adult and child end of life cancer care (Aburn et al, 2021; Cañadas‐De la Fuente et al, 2018; Gribben & Semple, 2020). Other authors acknowledge that managing distress, suffering, trauma, death, bereavement, anxiety and anger were common sources of emotional labour for haematology nurses (Kelly et al, 2000).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Caring for young patients who are dying clearly requires emotional labour for all nurses, which is in keeping with the literature more broadly concerning adult and child end of life cancer care (Aburn et al, 2021; Cañadas‐De la Fuente et al, 2018; Gribben & Semple, 2020). Other authors acknowledge that managing distress, suffering, trauma, death, bereavement, anxiety and anger were common sources of emotional labour for haematology nurses (Kelly et al, 2000).…”
Section: Discussionsupporting
confidence: 73%
“…Research has explored the emotional impact on nurses who care for adult and paediatric cancer patients (Aburn et al, 2021; Bowden et al, 2015; Cañadas‐De la Fuente et al, 2018; Pfaff et al, 2017), which are known to be fraught with emotional entanglement and challenges. Yet little is yet known about the experiences of ward‐based, early‐career nurses who care for AYAC and any emotional challenges this may bring.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for these buffering effects could be that humor in the workplace fosters cohesiveness among nurses [ 66 ]. In a study on the staff of a children’s blood and cancer center it was found that the feeling of belonging to a “work family” enhances resilience [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study was to capture and theorize the ways in which teachers in remote primary schools experience their work with children living with the effects of complex childhood trauma, with a view to informing university curriculum and education governance systems for initial teacher education and continuing professional development. The study used constructivist grounded theory (Charmaz, 2014) which is commonly utilized to investigate the lived experiences of participants (Karpouza and Emvalotis, 2019;Aburn et al, 2021;Causer et al, 2021;Hood and Copeland, 2021;Williams et al, 2021).…”
Section: Introductionmentioning
confidence: 99%